(untitled) (Journal of Pathology of Nepal, 2017)
A mixed adenoneuroendocrine carcinoma is a tumor composed of both adenocarcinoma and neuroendocrine carcinoma components, with each comprising at least one-third of the lesion, as defined by the World Health Organization classification of neuroendocrine neoplasms in 2010.. A 67-years-old male was admitted to the hospital with symptoms suggesting gastric cancer. Histopathology examination from endoscopic biopsy revealed adenocarcinoma. Later partial gastrectomy specimen examination the lesion show presence of well differentiated adenocarcinoma along with neuro endocrine carcinoma.